Relasi Sosial Madrasah Terhadap Perubahan Nilai Masyarakat Perbukitan - Ahmad Salim; Maragustam .; Radjasa . (LITERASI (Jurnal Ilmu Pendidikan), 2018)
The change of value is a reality that is has been occurred in society. Changes in one aspect of values will have implications for other aspects including activities that exist in madrasa, because madrasa is part of the sub-system of the community. Changes of respect value also occurs in the community around MI Maarif Kokap was located, precisely in the Menoreh hills of Yogyakarta, whereas this value is an important value that will affect the existence of the community itself.This article discusses the internalization of respect in MI Maarif Kokap Kulon Progo DIY. The results of the study show that respect internalization is carried out through classroom learning and activities that are routine and informal outside the classroom. These activities can effectively safeguard respect towards students, so students have a habit of implementing them. The success of respect internalization in MI Maarif can increase public trust in the existence of the madrasah.Keyword; internalization, change, value